2014
DOI: 10.2478/s11535-014-0350-x
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of microalgae can be enhanced by manipulating the cultivation temperature and irradiance

Abstract: The escalating levels of antibiotic resistance among pathogenic bacteria and the side effects of chemotherapeutic drugs in use forced the efforts of scientists to search for natural antimicrobial and anticancer substances with novel structures and unique mechanism of action. Focusing on bioproducts, recent trends in drug research have shown that microalgae (including the cyanobacteria) are promising organisms to furnish novel and safer biologically active compounds. Many microalgal metabolites have been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…Long-term adaptation mechanisms often involve metabolic shifts, consisting in the production of secondary metabolites [ 53 , 163 ]. Because stress conditions such as salinity [ 254 ], nutrient deficiency, temperature and high light stress [ 255 ] are “interpreted” by the algae as “dangerous” [ 91 ], they accumulate high-energy molecules such as carotenoids and/or lipids [ 13 , 53 , 254 , 256 ]. For instance, a nitrogen or silicon depletion stress has been shown to increase oil production in diatoms by a factor of 2 or 3 of their average dry weight [ 257 , 258 , 259 ].…”
Section: Understanding Of Diatom (Stress) Biologymentioning
confidence: 99%
“…Long-term adaptation mechanisms often involve metabolic shifts, consisting in the production of secondary metabolites [ 53 , 163 ]. Because stress conditions such as salinity [ 254 ], nutrient deficiency, temperature and high light stress [ 255 ] are “interpreted” by the algae as “dangerous” [ 91 ], they accumulate high-energy molecules such as carotenoids and/or lipids [ 13 , 53 , 254 , 256 ]. For instance, a nitrogen or silicon depletion stress has been shown to increase oil production in diatoms by a factor of 2 or 3 of their average dry weight [ 257 , 258 , 259 ].…”
Section: Understanding Of Diatom (Stress) Biologymentioning
confidence: 99%
“…against different types of bacteria, notably against S. aureus and S. xylosus. Furthermore, the results suggested that the harvesting period in terms of temperature and cell metabolism of the algae could play an important role in conferring the antibiotic effective against both Gram-positive and Gram-negative bacteria (Gacheva and Gigova, 2014) (Figure 8). The antibiotic activity of the ethanol extract of freshwater algae could be attributed to the presence of bioactive phenolics.…”
Section: Discussionmentioning
confidence: 99%
“…Under such constraints, microalgae are reported to produce a maximal amount of varied bioactives as compared to normal conditions due to the stressed altered metabolic pathways. The induction or overproduction of these bioactives is primarily a survival technique to overcome the inconsiderate growth environments [2]. It is thus, necessary to manipulate the growth conditions in order to stimulate the synthesis of commercially significant microalgal bioactives [3].…”
Section: Introductionmentioning
confidence: 99%